Executive function and emergent mathematical skills among preschool children in Singapore : updating, shifting and inhibitory control - Yeo, Ke Xin (2015)
The current study examined how executive functioning components, updating, shifting and inhibitory control influence the development of emergent mathematical skills among preschool children in Singapore. Two hundred and fifteen preschoolers (128 males, 87 females) aged between 39 to 75 months were recruited. Each participant completed three executive function tasks, including the Auditory Working Memory (AWM) task, Flexible Item Selection Task (FIST) and Go/No-Go task and two math achievement tasks, such as the Quantitative Concepts (QC) test and Applied Problems (AP) test from the Woodcock-Johnson Test of Achievement III. Hierarchical regression analyses revealed general executive functioning and updating ability to significantly predict math achievement after controlling for individual differences in gender, age, ethnicity, number of languages spoken and contextual variables of kindergarten attended and socioeconomic status.